2006
DOI: 10.1038/sj.ki.5001663
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of uremic serum-induced expression of bone matrix proteins in bovine vascular smooth muscle cells

Abstract: We have previously found that uremic human serum upregulates RUNX2 in vascular smooth muscle cells (VSMCs), and that RUNX2 is upregulated in areas of vascular calcification in vivo. To confirm the role of RUNX2, we transiently transfected a dominant-negative RUNX2 (DeltaRUNX2) construct in bovine vascular smooth muscle cells (BVSMCs). Blocking RUNX2 transcriptional activity significantly decreased uremic serum induced alkaline phosphatase (ALP) activity (268+/-34 vs 188+/-9.5 U/g protein, P<0.05) and osteocalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 45 publications
(67 reference statements)
11
88
0
4
Order By: Relevance
“…BMP-2 has been previously observed to enhance phosphate-induced calcification of bovine SMC [13]. Therefore, we first confirmed that human SMC contained BMP receptors, and that BMP-2 could enhance phosphate-induced calcification in these cells.…”
Section: Expression Of Bmp Receptors In Human Smcsupporting
confidence: 69%
See 2 more Smart Citations
“…BMP-2 has been previously observed to enhance phosphate-induced calcification of bovine SMC [13]. Therefore, we first confirmed that human SMC contained BMP receptors, and that BMP-2 could enhance phosphate-induced calcification in these cells.…”
Section: Expression Of Bmp Receptors In Human Smcsupporting
confidence: 69%
“…BMP-2 was also expressed in calcified arteries of LDLR −/− mice fed a high-fat diet [11]. In addition, treatment of calcifying vascular cells or bovine smooth muscle cells in vitro with BMP-2 resulted in enhanced calcification [12,13]. Finally, mice with targeteddeletion of Smad6, an inhibitory Smad in the BMP2 signaling cascade, present with vascular calcification [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA binding sites of Runx2 have been identified in the genes of major bone matrix proteins including Col I and OC, and Runx2 induces the expression of these genes or activates their promoters in osteoblasts (21,63). Blocking Runx2 transcriptional activity by a dominant-negative Runx2 has been shown to decrease uremic serum-induced ALP activity and OC expression (28). Consistently, we found that increased expression of ALP, Col I, and OC was associated with increased Runx2 during VSMC calcification (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Runx2 expression has been identified in atherosclerotic calcified human vascular tissue specimens (24 -26) and in calcifying aortic smooth muscle cells in mice (16) but not in normal vessels. Furthermore, increased expression of Runx2 is associated with VSMC calcification in vitro (16,27,28), supporting a role for Runx2 in vascular calcification. However, the potential link between Runx2 regulation and oxidative stress-induced vascular calcification has not been examined.…”
mentioning
confidence: 99%